PHYSALIS GROWTH, DEVELOPMENT AND YIELD AT DIFFERENT SOWING SEASONS IN THE BRAZILIAN NORTHEASTERN SEMIARID (Colloquium Agrariae. ISSN: 1809-8215, 2021)
The Physalis genus is composed of species with economic and medicinal importance, its cultivation is expanding in Brazil, and is needed research on the performance of species in different regions of the country. Thus, the objective was to characterize the growth, development and yield of Physalis angulata and Physalis ixocarpa species cultivated in three sowing seasons in Bahia's semiarid region. The days after sowing were determined for the occurrence of vegetative and reproductive stages, and the length and diameter of the main branch were evaluated weekly. At the end of cultivation, the number and total weight of fruits per plant were determined. The plants sown in April showed the best results, with acceleration in flowering, higher productivity and growth close to other producing regions, which is the best period for the cultivation of species. P. angulata is a more tolerant species and can be sown at different periods without compromising yield. High temperatures combined with scarcity of rainfall compromise the development of plants of both species.